2020
DOI: 10.3390/plants9050586
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the SAM Synthetase Gene Family and Its Roles in Tomato Seedlings under Abiotic Stresses and Hormone Treatments

Abstract: S-Adenosyl-L-methionine (SAM) is a key enzyme involved in many important biological processes, such as ethylene and polyamine biosynthesis, transmethylation, and transsulfuration. Here, the SAM synthetase (SAMS) gene family was studied in ten different plants (Arabidopsis, tomato, eggplant, sunflower, Medicago truncatula, soybean, rice, barley, Triticum urartu and sorghum) with respect to its physical structure, physicochemical characteristics, and post-transcriptional and post-translational modifications. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 67 publications
0
34
0
Order By: Relevance
“…Various abiotic and biotic stresses, such as plant pathogens, drought, cold, heat, and salinity, have destructive effects on the growth and development of plant species. Plants employ complex regulatory pathways to address various stimuli, which include stress sensing, signal transduction, and regulation of stress-responsive genes and/or proteins eventually manifested at the cellular and physiological levels [1,2]. The modulation of gene expression in response to stresses is highly controlled by specific transcription factors (TFs), which simultaneously mediate the transcription of a vast number of downstream stress-responsive genes [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Various abiotic and biotic stresses, such as plant pathogens, drought, cold, heat, and salinity, have destructive effects on the growth and development of plant species. Plants employ complex regulatory pathways to address various stimuli, which include stress sensing, signal transduction, and regulation of stress-responsive genes and/or proteins eventually manifested at the cellular and physiological levels [1,2]. The modulation of gene expression in response to stresses is highly controlled by specific transcription factors (TFs), which simultaneously mediate the transcription of a vast number of downstream stress-responsive genes [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings revealed that PHTs in C. sativa with their orthologues in Arabidopsis and rice could be classified into seven different groups that PHTs in rice showed the high distance from studied dicot species. These results illustrate that probably PHT genes of dicot plants are derived from PHT genes of monocot species (Faraji et al, 2020;Heidari et al, 2020a).…”
Section: Discussionmentioning
confidence: 55%
“…In general, PHOs1 and their homologs were predicted with high potential N-glycosylation and phosphorylation sites. Post-translation modifications such as phosphorylation processes cause significant effects on protein activities and inducing cell signaling (Heidari et al, 2020a;Silva-Sanchez et al, 2015). The high phosphorylation potential of PHO1 proteins may indicate that these proteins are involved in various cellular processes under signal transduction pathways (Ahmadizadeh et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…We predicted phosphorylation sites in all tcGASA, ranging in number from 7 to 57. The phosphorylation of proteins is also vital for cell signaling, regulation of various protein mechanisms, and as a substrate for various kinases (Heidari et al, 2020; Nawaz et al, 2019; Silva-Sanchez et al, 2015). Hence, tcGASA may be a good target for various studies to elucidate their complete role.…”
Section: Discussionmentioning
confidence: 99%